2017
DOI: 10.21037/atm.2017.03.01
|View full text |Cite
|
Sign up to set email alerts
|

Use of distal perfusion in peripheral extracorporeal membrane oxygenation

Abstract: Extra corporeal membrane oxygenation (ECMO) is a life-saving technique to manage refractory cardiopulmonary failure. Its usage and indication continue to increase. Femoral venoarterial ECMO (VA ECMO) is relatively less invasive and the cardiac support may be more rapidly instituted in in these extremely tenuous patients. Vascular injuries and limb ischemia unfortunately occur in these emergent access settings. Here we will discuss the optimal techniques of preventing this complication which might affect patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 22 publications
0
32
0
Order By: Relevance
“…This attention is further reduced due to the results of studies such as a meta-analysis with 1866 patients in VA ECMO who reported a 16.9% incidence of lower extremity ischemia. 18 It is assessed that, in this situation, the ECMO team intervene, as the specialist nurses identified early the reduction of the perfusion of the catheterized limb signaling it to the medical staff, making it necessary to change the device.…”
Section: Objective Methodsmentioning
confidence: 99%
“…This attention is further reduced due to the results of studies such as a meta-analysis with 1866 patients in VA ECMO who reported a 16.9% incidence of lower extremity ischemia. 18 It is assessed that, in this situation, the ECMO team intervene, as the specialist nurses identified early the reduction of the perfusion of the catheterized limb signaling it to the medical staff, making it necessary to change the device.…”
Section: Objective Methodsmentioning
confidence: 99%
“…The risk can be minimized with placement of a distal perfusion cannula or by cannulating the femoral artery via a chimney graft. 16 In veno-venoarterial ECMO, a second venous drainage cannula is placed (such that there are now drainage cannulae within both the IVC via the femoral vein and the SVC via the internal jugular vein), and the 2 venous cannulae are connected via a Y-adapter. In venoarterial-venous ECMO, oxygenated blood is returned to both an arterial cannula and a separate venous delivery cannula commonly placed via the jugular vein.…”
Section: Types Of Ecmo and Cannulation Optionsmentioning
confidence: 99%
“…Femoral arterial cannulation carries an increased risk of profound distal limb ischemia. Some of the causes that lead to lower limb ischemia during ECMO support are acute embolism, dissection/perforation or rupture of the common femoral artery (CFA) or the iliac artery, thrombosis, pseudoaneurysm, hyperperfusion, and ischemia after decannulation usually due to distal embolization [22]. This problem has been solved to a large extent by prophylactically placing an ipsilateral perfusion catheter [22].…”
Section: Limb Ischemiamentioning
confidence: 99%
“…Some of the causes that lead to lower limb ischemia during ECMO support are acute embolism, dissection/perforation or rupture of the common femoral artery (CFA) or the iliac artery, thrombosis, pseudoaneurysm, hyperperfusion, and ischemia after decannulation usually due to distal embolization [22]. This problem has been solved to a large extent by prophylactically placing an ipsilateral perfusion catheter [22]. In a small study using 43 patients who underwent femoral artery cannulation, placement of a prophylactic superficial femoral artery [SFA] catheter in ten patients produced no limb ischemia.…”
Section: Limb Ischemiamentioning
confidence: 99%